Exposure to internet pornography and sexually aggressive behaviour: protective roles of social support among Korean adolescents. Issue 2 (4th May 2019) - Shin, Junseob; Lee, Chung Hwan
ABSTRACT: Adolescents' exposure to internet pornography and its negative effects on healthy sexual development have been extensively investigated. However, little research has addressed the identification of protective factors that can buffer these negative effects. Based on the conceptualisation of a stress-buffering model of social support, this study empirically tested whether social support would provide a buffer against negative effects of internet pornography on sexually aggressive behaviours in adolescents. Results from an online survey of two-hundred-ten (210) Korean high school students revealed that social support from parents and friends performed buffering roles, and the buffering effect of friend support was the strongest. Based on these results, practical implications for healthy adolescent sexual development were discussed.